EFEKTIVITAS PELATIHAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA PADA LEMBAGA PENDIDIKAN - Ilham Wahyudi; Syahril Yusuf; Rustam; Maynur; Afriza (Program Studi Manajemen Pendidikan Islam, 2022)
This research analyzes the effectiveness of HR training and development in educational institutions through a literature study. Data were collected from the literature and analyzed qualitatively with content analysis, including definitions, objectives, types, processes, and program effectiveness. Training and development aims to improve the skills, competencies and productivity of educators and education personnel in order to achieve educational goals efficiently. Training methods include on the job training and off the job training. The effectiveness of the program is measured through evaluation before, during and after implementation, with indicators of increased knowledge, behavioural changes and improved institutional performance. Success is reflected in improved teacher performance, student achievement and achievement of national education standards. The study concludes that effective training has a significant impact on institutions and service users, emphasizing the importance of continuous evaluation to ensure program relevance and impact